Influence of arterial hypertension, smoking, and their combination on mortality (according to the results of a 27-year cohort prospective study of the unorganized population of Tomsk) - I. V. Dolgalev; N. G. Brazovskaya; A. Yu. Ivanova; A. Yu. Shipkhineeva; P. M. Bogaychuk (Российский кардиологический журнал, 2019)
Aim. To study the influence of arterial hypertension (AH), smoking, and their combination on the risk of all cause and cardiovascular mortality.Material and methods. We conducted a 27-year cohort prospective study of the unorganized population of Tomsk (916 women and 630 men aged 20-59 years). At the first stage, we studied the prevalence of AH and smoking (1998-1991), at the second (2015) — the effect of these risk factors (RF) and their combination on the risk of all cause and cardiovascular mortality. AH was diagnosed at a blood pressure level of >140/90 mmHg and <140/90 mm Hg in individuals taking antihypertensive drugs. Smokers were individuals who smoked at least 1 cigarette per day and quit smoking less than one year ago.Results. The study found a significant effect of AH and smoking on mortality: the relative risk (RR) of all-cause mortality in people with hypertension was 2,2, in smokers — 2,3, in those with a combination of RF — 5,0. The RR of cardiovascular mortality in AH individuals was 3,4, in smokers — 1,6, in smoking men and women suffering from AH — 5,2. An increase in the risk of all-cause mortality in people with AH and smoking was observed in all gender-age groups. Smoking was found to increase the risk of all-cause mortality in individuals with high levels of blood pressure by 2,1 times compared with non-smoking hypertensive patients. It reduces the chances of a 27-year survival rate to 64,4%, and more so in the youngest (20-39 years) age group (RR — 3,9). Multivariate analysis showed that AH and smoking make the most significant contribution to the formation of mortality compared to other modifiable RFs.Conclusion. We found that AH and smoking are among the most influential RFs, and their combination increases the RR of all-cause mortality by 5,0 times (cardiovascular — 5,2 times). We also determined an additional risk of smoking in individuals suffering from AH to the all-cause mortality.